PENGARUH PENAMBAHAN TEMPE PADA KARAKTERISTIK MUTU JELLY TEMPE - Ni_Luh Putu Prastithi; Badrut Tamam; I_Gusti Putu Sudita_Puryana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
Tempe is a traditional food that is produced from fermented soybean seeds or some other ingredients. Fermentation uses several types of Rhizopus molds, such as Rhizopus oligosporus, Rhizopus oryzae, Rhizopus stolonifer and several other types of Rhizopus molds. In making tempeh jelly uses a mixture of agar and tempeh as its main component. Tempeh jelly is cooked in a round shape. Comparison of wheat flour and tempeh can add nutritional value to tempeh jelly. This study aims to determine the organoleptic characteristics including color, aroma, taste, texture, and calculate the nutrient content produced in 1 portion of the best jelly tempe. This study uses an experimental method with the type of Randomized Block Design. There are 5 treatments with a ratio of 5 g agar and tempeh 0 g, 10 g, 20 g, 30 g, 40 g. Based on the Variety of Jelly Tempe the best is P2withcolor2,60,aroma2,67,taste,2,96,texture,2,73  Keywords: Tempe, agar, jelly tempe, organoleptic